Egg size and fecundity of yellowstripe scad (Selaroides leptolepis Cuvier) from Surigao Del Sur - Decrepito, Ma. Theresa Ruth M. (2018.)
The yellowstripe scad (Selaroides leptolepis) is a fish with high commercial value. The fecundity and egg size of yellowstripe scad from Surigao del Sur were studied in order to gain information on the reproductive aspect of the S. leptolepis. Total fecundity of the fish was determined using gravimetric method and the egg sizes measured using the ImageJ oublic domain software. Analyses of correlation between fecundity and standard length, gonad weight, body weight, or the GSI were done using linear regression and ANOVA. Results show that fecundity ranges from 5,051 to 67,346 eggs of size range 9.1-14.0 cm SL. Egg sizes ranges from 166.9 ? 588.2 µm. there is a weak linear relationship between fecundity and standard length, moderate between fecundity and body weight, and strong relationship between fecundity and gonad weight with correlation coefficient of 0.1983, 0.2653, and 0.9093 respectively. There is also a strong linear relationship between fecundity and GSI. Information gathered from this study contributes valuable knowledge to the reproductive biology of yellowstripe scad and establish regulations on its fisheries management.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas.
Keywords: Scad, Yellowstripe -- Eggs -- Surigao Del Sur -- Research; Scad, Yellowstripe -- Fecundity -- Surigao Del Sur -- Research